Crystal structure of monomeric Amuc_1100 from Akkermansia muciniphila. Issue 4 (7th April 2020) - Mou, Luqiu; Peng, Xi; Chen, Yan; Xiao, Qingjie; Liao, Huijuan; Liu, Mingfeng; Guo, Li; Liu, Yang; Zhang, Xiaohu; Deng, Dong
Abstract : The crystal structure of monomeric Amuc_1100 (residues 31–317) is reported at 2.1 Å resolution. Structural investigation of Amuc_1100 will shed light on the therapeutic mechanism of Akkermansia muciniphila as well as the formation of its type IV pilus‐like structure. Abstract : Many human diseases, such as obesity and diabetes, show annual increases in prevalence and often involve intestinal microbes. One such probiotic bacterium, Akkermansia muciniphila, which was discovered a decade ago, has been reported to influence glucose homeostasis and to contribute to gut health. Amuc_1100, a functionally uncharacterized protein of A. muciniphila, was found to be a key active component in reducing the body weight of mice. Here, the crystal structure of Amuc_1100 (residues 31–317), referred to as Amuc_1100*, is reported at 2.1 Å resolution. Amuc_1100* has a similar fold to three proteins related to pilus formation, PilO, PilN and EpsL, indicating a similar function. Biochemical investigations further confirmed a monomeric state for the soluble region of Amuc_1100, which differs from the dimeric states of PilO, PilN and EpsL. This study provides a structural basis for the elucidation of the molecular mechanism of Amuc_1100.